Hypothermia protects human neurons. Issue 5 (3rd January 2014) - Antonic, Ana; Dottori, Mirella; Leung, Jessie; Sidon, Kate; Batchelor, Peter E.; Wilson, William; Macleod, Malcolm R.; Howells, David W.
<x xml:space="preserve">Abstract</x> Background and Aims Hypothermia provides neuroprotection after cardiac arrest, hypoxic‐ischemic encephalopathy, and in animal models of ischemic stroke. However, as drug development for stroke has been beset by translational failure, we sought additional evidence that hypothermia protects human neurons against ischemic injury. Methods Human embryonic stem cells were cultured and differentiated to provide a source of neurons expressing β III tubulin, microtubule‐associated protein 2, and the Neuronal Nuclei antigen. Oxygen deprivation, oxygen‐glucose deprivation, and H2O2‐induced oxidative stress were used to induce relevant injury. Results Hypothermia to 33°C protected these human neurons against H2O2‐induced oxidative stress reducing lactate dehydrogenase release and Terminal deoxynucleotidyl transferase dUTP nick end labeling‐staining by 53% (P ≤ 0·0001; 95% confidence interval 34·8–71·04) and 42% (P ≤ 0·0001; 95% confidence interval 27·5–56·6), respectively, after 24 h in culture. Hypothermia provided similar protection against oxygen‐glucose deprivation (42%, P ≤ 0·001, 95% confidence interval 18·3–71·3 and 26%, P ≤ 0·001; 95% confidence interval 12·4–52·2, respectively) but provided no protection against oxygen deprivation alone. Protection (21%) persisted against H2O2‐induced oxidative stress even when hypothermia was initiated six‐hours after onset of injury (P ≤ 0·05; 95% confidence interval 0·57–43·1). Conclusion We conclude that hypothermia protects stem cell‐derived human neurons against insults relevant to stroke over a clinically relevant time frame. Protection against H2O2‐induced injury and combined oxygen and glucose deprivation but not against oxygen deprivation alone suggests an interaction in which protection benefits from reduction in available glucose under some but not all circumstances.